Highly dynamic wintering strategies in migratory geese: Coping with environmental change - Clausen, Kevin K.; Madsen, Jesper; Cottaar, Fred; Kuijken, Eckhart; Verscheure, Christine (Global change biology, 2018)
When and where to move is a fundamental decision to migratory birds, and the fitness‐related costs and benefits of migratory choices make them subject to strong selective forces. Site use and migration routes are outcomes of opportunities in the surrounding landscape, and the optimal migration strategy may be conservative or explorative depending on the variability in the environment occupied by the species. This study applies 25 years of resighting data to examine development in winter migration strategy of pink‐footed geese divided among Denmark, the Netherlands and Belgium, and analyse potential drivers of strategy change as well as individuals’ likelihood to break with migratory tradition. Contrary with the general notion that geese are highly traditional in their winter site use, our results reveal that winter migration strategy is highly dynamic in this species, with an average annual probability of changing strategy of 54%. Strategy was not related to hunting pressure or winter temperature, but could be partly explained by a tracking of food resources in a landscape of rapid land use changes. The probability of individuals changing strategy from year to year varied considerably between birds, and was partly related to sex and age, with young males being the most likely to change. The annual probability of changing wintering strategy increased substantially from ≈40% to ≈60% during the study period, indicating an increasingly explorative behaviour. Our findings demonstrate that individual winter strategies are very flexible and able to change over time, suggesting that phenotypic plasticity and cultural transmission are important drivers of strategy choice in this species. Growing benefits from exploratory behaviours, including the ability to track rapid land use changes, may ultimately result in increased resilience to global change. Based on 25 years of resightings of a migratory goose species, the pink‐footed goose, we find that wintering strategies have become increasingly dynamic and that strategy choice changes over time. This appears to be primarily linked to rapid changes in agricultural land use, while changes in hunting pressure did not play a major role, best exemplified by the increasing use of western Denmark as a sole wintering area.